Nutritional recommendations for synchronized swimming - Robertson, S.; Benardot, D.; Mountjoy, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
The sport of synchronized swimming is unique, because it combines speed, power, and endurance with precise synchronized movements and high-risk acrobatic maneuvers. Athletes must train and compete while spend- ing a great amount of time underwater, upside down, and without the luxury of easily available oxygen. This review assesses the scientific evidence with respect to the physiological demands, energy expenditure, and body composition in these athletes. The role of appropriate energy requirements and guidelines for carbohydrate, protein, fat, and micronutrients for elite synchronized swimmers are reviewed. Because of the aesthetic nature of the sport, which prioritizes leanness, the risks of energy and macronutrient deficiencies are of significant concern. Relative Energy Deficiency in Sport and disordered eating/eating disorders are also of concern for these female athletes. An approach to the healthy management of body composition in synchronized swimming is outlined. Synchronized swimmers should be encouraged to consume a well-balanced diet with sufficient energy to meet demands and to time the intake of carbohydrate, protein, and fat to optimize performance and body composition. Micronutrients of concern for this female athlete population include iron, calcium, and vitamin D. This article reviews the physiological demands of synchronized swimming and makes nutritional recommendations for recovery, training, and competition to help optimize athletic performance and to reduce risks for weight-related medical issues that are of particular concern for elite synchronized swimmers.